Psychological immunity and its relation to life stress among mothers of students with Learning disabilities - Alshaimaa Abdelsattar Hamid Agramia (International Journal of Instructional Technology and Educational Studies)
This research aims to detect the relationship between psychological immunity and life stress among mothers of students with learning disabilities at primary stage. The researcher used the Psychological Immunity Scale(prepared by the researcher)and Life Stress Scale(prepared by Sayed Ahmed Elbahas,2017).These instruments were applied to a sample consisting of (100) mothers of students with learning disabilities at primary stage.The research results reveal that there is a negative relationship between scores of the mothers on both the two scales psychological immunity and life stress on the dimensions and the total score. There are a statistically differences between mothers of students with learning disabilities who have high levels of psychological immunity and who have low levels at feeling with life stress in favor of mothers with low levels. There are statistically differences at levels of feeling with life stress with mothers of students with learning disabilities due to socioeconomical levels(high-low).Psychological immunity-life stress-mothers of learning disabilities students